Numerical Analysis of Thermal and Moisture Bridges in Insulation Filled Masonry Walls and Corner Joints - Nagy, Balázs; Stocker, György (Periodica Polytechnica Civil Engineering, 2019)
In recent years, thermal insulation filled masonry blocks have become widespread in Central-Europe. These blocks can satisfy thermal performance requirements without the need of additional insulation. However, these requirements in the building regulations only consider thermal, but neglect moisture aspects. This paper presents a comparative analysis of steady-state numerical conjugated heat- and moisture transport FEM simulations of masonry walls. The hygrothermal material properties of the insulation filled masonry blocks were measured in laboratory. In the paper, besides a wall section, a wall corner joint is presented, both modeled in 2D from complex building elements, such as insulation filled blocks, and were tested using different fillers (aerogel, expanded perlite, expanded polystyrene, mineral wool and PUR foam), respectively. Monthly variation of the fillers’ thermal conductivity, thermal and moisture transmittance and effective water vapor diffusion resistance of the walls, as well as linear thermal and moisture transmittance of the wall corner joints were examined in details. A comparison between detailed and simplified modeling were also carried out. The evaluation of the results shows that there are noticeable differences in trends between thermal and moisture transmittances, latter show significantly greater variation and depends mainly on the hygrothermal behavior of the filler. Based on effective water vapor resistance factors, we showed that assuming the same vapor transmission properties for all type of filled masonry blocks is a mistake.